Risk-based decision-making in the treatment of HER2-positive early breast cancer: Recommendations based on the current state of knowledge. (September 2021) - Jackisch, Christian; Cortazar, Patricia; Geyer, Charles E.; Gianni, Luca; Gligorov, Joseph; Machackova, Zuzana; Perez, Edith A.; Schneeweiss, Andreas; Tolaney, Sara M.; Untch, Michael; Wardley, Andrew; Piccart, Martine
Highlights: Risk of relapse must be evaluated to optimise treatment for HER2-positive early breast cancer. Decision about whether to offer neoadjuvant chemotherapy plus pertuzumab–trastuzumab. Patients with a pathological complete response continue HER2-targeted therapy to complete 18 cycles (before and after surgery). Patients with residual disease after standard-of-care neoadjuvant chemotherapy plus HER2-targeted therapy should receive post-neoadjuvant trastuzumab emtansine to complete 14 cycles (after surgery). For patients who undergo surgery first, treatment with adjuvant chemotherapy plus pertuzumab–trastuzumab is the standard of care for those patients with a higher risk of relapse. For patients with node-negative disease and tumours <2 cm at presentation, paclitaxel for 12 weeks plus 18 cycles of trastuzumab might be a good option for the post-operative adjuvant therapy. Abstract: Treatment of HER2-positive early breast cancer (EBC) continues to evolve with neoadjuvant (pre-operative) and adjuvant (post-operative) HER2-targeted therapies as standard of care. There are two important decision points. The first involves deciding between neoadjuvant therapy or proceeding directly to surgery. Neoadjuvant chemotherapy (NACT) plus pertuzumab–trastuzumab is appropriate for patients with high-risk HER2-positive EBC (tumour diameter ≥2 cm, and/or node-positive disease). Patients with node-negative disease and tumour diameter <2 cm are candidates for upfront surgery followed by paclitaxel for 12 weeks plus 18 cycles of trastuzumab, with the option to add pertuzumab (if pN+). The second decision point involves the pathohistological result at surgery after neoadjuvant therapy. Total pathological complete response (tpCR: ypT0/is, ypN0) is associated with improved survival endpoints. Patients with tumours ≥2 cm and/or node-positive disease at diagnosis who have a tpCR after dual blockade should continue pertuzumab–trastuzumab in the adjuvant setting to complete 1 year (18 cycles) of treatment. For patients with invasive residual disease, 14 cycles of post-neoadjuvant trastuzumab emtansine (T-DM1) therapy significantly increases invasive-DFS compared with trastuzumab. Extended adjuvant therapy with neratinib is an option in selected patients (HER2-positive and oestrogen receptor [ER]-positive) who have completed adjuvant trastuzumab-based therapy. Less aggressive chemotherapy regimens are recommended in populations with a lower risk of recurrence (patients with small tumours without axillary involvement; patients unlikely to tolerate anthracycline-taxane or taxane-carboplatin regimens). Ultimately, treatment recommendations should be consistent with local and international guidelines. Further studies will guide optimisation of treatment for patients with HER2-positive EBC according to the risk of disease recurrence.